Generation Z and the Use of Digital Technology: A Review from 2014 to 2023 - Febliza, Asyti; Kadarohman*, Asep; Aisyah, Siti; Abdullah, Norazilawati (Universitas Syiah Kuala, 2025)
Generation Z or igeneration or post-millenials are referred to as true digital natives due to the influence of technology in their lives. The number of gen Z enrolled in higher education institutions is increasing every year, making dealing with them a significant problem for institutions. Therefore, this study aims to identify the digital technologies used by gen Z across various educational levels, subjects, and the role of technology in learning. This systematic review focuses on the latest research from 2014 to 2023 on Generation Z and the use of technology. The study was conducted by systematically searching with related keywords (generation Z* and *educational technology) which found relevant studies on ERIC. The 16 articles obtained and were coded. The article search process and screening process based on the Prisma flow diagram. The results showed that: the largest percentage of the type of technology used by generation Z is social media, the majority of participants adopted in the articles were higher education students, the dominating disciplines in these articles are not-specified and technology is widely used to determine students' behavior, not learning achievements in academics. Recommendations are also included in this study